PRZYCZYNEK DO HISTORII PROSTYTUCJI ORAZ CHORÓB WENERYCZNYCH W GUBERNII PIOTRKOWSKIEJ NA PRZEŁOMIE XIX I XX WIEKU - Gotowicz, Aleksander (In Gremium. Studies in History, Culture and Politics, 2012)
CONTRIBUTION TO THE HISTORY OF PROSTITUTION AND VENEREAL DISEASES IN THE PIOTRKOWSKA PROVINCE ON THE TURN OF THE 19th AND 20th CENTURIES The article deals with the phenomenon of prostitution and the scale of occurrence of venereal diseases in the Piotrkowska province on the turn of the 19th and 20th centuries. Issues like the number of women engaged in prostitution, the number of brothels and their location in particular areas are addressed on the basis of yearly reports of the Medical Department of the Russian Ministry of Interior (which have not yet been used in Polish historiography in reference to this topic) and the national census from 1897. The article also deals with the factors which influence the decision of getting engaged in prostitution and the nature of prostitution itself. Moreover, the scale of occurrences of sexually transmitted diseases in particular towns and counties of the analysed district is outlined in the article. In addition to its main area of interest, the article points out the phenomenon of prostitution of homosexual character and the issue of procuring towards minors, which have not yet been a subject of any historical reflection in Poland.